Contrasting Responses of Protistan Plant Parasites and Phagotrophs to Ecosystems, Land Management and Soil Properties - Fiore-Donno, Anna Maria; Richter-Heitmann, Tim; Bonkowski, Michael (Frontiers in Microbiology, 2020)
Functional traits are increasingly used in ecology to link the structure of microbial communities to ecosystem processes. We investigated two important protistan lineages, Cercozoa and Endomyxa (Rhizaria) in soil using Illumina sequencing and analysed their diversity and functional traits along with their responses to environmental factors in grassland and forest across Germany. From 600 soil samples, we obtained 2,101 Operational Taxonomy Units representing ~18 million Illumina reads (region V4, 18S rRNA gene). All major taxonomic and functional groups were present, dominated by small bacterivorous flagellates (Glissomonadida). Endomyxan plant parasites were absent from forest. In grassland, they were promoted by more intensive land use management. Grassland and forest strikingly differed in community composition. Relative abundances of bacterivores and eukaryvores were contrastingly influenced by environmental factors, indicating bottom-up regulation by food resources. These patterns provide new insights into the functional organization of soil biota and indications for a more sustainable land-use management.